Pengaruh Diskon, Live Streaming Selling dan Online Customer Review Terhadap Keputusan Pembelian Produk Skincare The Originote (Studi Pada Marketplace Shopee) - Lestari, Ane; Jaya, Rama Chandra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The development of internet technology has had a significant impact on the growth of social networks. In today's digital era, social networks have become one of the main components that prioritize interaction between individuals. This study aims to analyze the Effect of Discounts, Live Streaming Selling, and Online Customer Reviews on Purchase Decisions for The Originote Skincare Products (Study on the Shopee Marketplace). The method used in this study is a quantitative method with a descriptive and verification approach, the sampling technique used is Purposive Sampling with a sample using the Cochran formula which produces 100 respondents. The results of the study indicate that Discounts and Live Streaming Selling have a positive and significant effect on Purchase Decisions, while Online Customer Reviews do not have a significant effect on Purchase Decisions. Simultaneously contributing 57.6% While the remaining 42.4% is influenced by other variables not discussed in this study. Based on these findings, it is recommended that companies utilize discount strategies at certain moments, optimize live streaming selling with interactive host training, and manage customer reviews with fast and professional responses. This research is expected to be a reference for developing marketing strategies in the digital era, as well as encouraging further research by adding variables such as brand image or social media marketing for more comprehensive results.